A Janus-Faced Bacterium: Host-Beneficial and -Detrimental Roles of Cutibacterium acnes - Brüggemann, Holger; Salar-Vidal, Llanos; Gollnick, Harald P. M.; Lood, Rolf (Frontiers in Microbiology, 2021)
The bacterial species Cutibacterium acnes (formerly known as Propionibacterium acnes) is tightly associated with humans. It is the dominant bacterium in sebaceous regions of the human skin, where it preferentially colonizes the pilosebaceous unit. Multiple strains of C. acnes that belong to phylogenetically distinct types can co-exist. In this review we summarize and discuss the current knowledge of C. acnes regarding bacterial properties and traits that allow host colonization and play major roles in host-bacterium interactions and also regarding the host responses that C. acnes can trigger. These responses can have beneficial or detrimental consequences for the host. In the first part of the review, we highlight and critically review disease associations of C. acnes, in particular acne vulgaris, implant-associated infections and native infections. Here, we also analyse the current evidence for a direct or indirect role of a C. acnes-related dysbiosis in disease development or progression, i.e. reduced C. acnes strain diversity and/or the predominance of a certain phylotype. In the second part of the review, we highlight historical and recent findings demonstrating beneficial aspects of colonization by C. acnes such as colonization resistance, immune system interactions, and oxidant protection, and discuss the molecular mechanisms behind these effects. This new insight led to efforts in skin microbiota manipulation, such as the use of C. acnes strains as probiotic options to treat skin disorders.